Model-based performance study of an industrial single spool gas turbine 9EA-GT by changing the inlet guide vane angle and modifying the compressor map - Alblawi, Adel (Frontiers in Mechanical Engineering, 2024)
In this paper, an industrial gas turbine engine with a single spool (single spool 9EA-GT) is discussed in this study along with a thermodynamic model for computing steady-state performance. In addition, a novel component map production method is developed for this model for a different compressor and turbine by downloading from the GasTurb12 tool and scaling to the compressor and turbine's design point for the investigation of a gas turbine engine (GTE). A control system of engine flow capacitance by changing inlet guide vanes (IGV) is presented. Adjusting the IGVs controllable blades are used to optimize all the engine units by continuously correcting the compressor features map.The airflow via the compressor, which in turn controls the airflow throughout the entire system, is managed by IGVs. The computations for steady-state performance involve two models: steady-state behavior at engine commencing (from 65% to 100% speed, without load), and steady-state behavior while loading (continuous speed of 100%). In this model, the challenges brought by the lack of understanding of stage-by-stage performance are resolved by building artificial machine maps using suitable scaling methods to generalized maps derived from the previous research and validating them with experimental observations from real power plants. The engine performance simulation utilizing the maps' employing MATLAB is carried out. Assessment results are found to be in good agreement with the actual performance data. During a steady start, the control system used in this study decreased the fuel consumption, exhaust gas mass flow rate, and compressor-driven power for the GTE by 9.5 %, 19.3 % and 37.5 % respectively, while it decreased by 1 %, 12.2 % and 19.7 % respectively when loading the engine.